Associated Risk Factors for Asymptomatic Bacteriuria in Pregnant Women Visited Antenatal Clinic in Lahore, Pakistan - Sana Noor, Noor Shahid, Jennifer Jacob, Sara Rasheed, Tazeem Akhter, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Asymptomatic bacteriuria is the occurrence of bacteria in the urine sample without any clinical symptoms. The odds of asymptomatic bacteriuria increase due to the hormonal growth during pregnancy. Methodology: The data was collected from a sample of size 167 pregnant women using self-structured questionnaire. The questionnaire was based on two sections. The questionnaire was tested using Cronbach alpha. The data was collected using convenient sampling. The frequency distribution of the risk factors was given. The binary logistic regression analysis was performed to access the major risk factors that enhance the odds for asymptomatic bacteriuria in pregnant women. Results: The past history of UTI was seen as a significant risk factor. The overall incidence of asymptomatic bacteriuria was found in 22 pregnant women and among these, approximately 9% had past history of UTI. About 44.9% of the pregnant women showed a past history of UTI. Conclusion: Most of the pregnant women fall in the age group 26-32 years. The significant factor is age group for asymptomatic bacteriuria. Advancement in age enhance the odds for the asymptomatic bacteriuria. History of UTI is found as a significant risk factor. Keywords: Asymptomatic bacteriuria, pregnancy, infections,